2023
DOI: 10.3390/cryst13050712
|View full text |Cite
|
Sign up to set email alerts
|

Metal-Involving Halogen Bonding Confirmed Using DFT Calculations with Periodic Boundary Conditions

Abstract: The cocrystallization of trans-[PtI2(NCN(CH2)5)2] and iodoform (CHI3) yields crystalline adduct trans-[PtI2(NCN(CH2)5)2]∙2CHI3, the structure of which was studied via single-crystal X-ray diffractometry (XRD). In the XRD structure of trans-[PtI2(NCN(CH2)5)2]∙2CHI3, apart from rather predictable C–H∙∙∙I hydrogen bonds (HBs) and C−I∙∙∙I halogen bonds (XBs) with the iodide ligands, we identified C–I∙∙∙Pt metal-involving XBs, where the platinum center functions as an XB acceptor (that includes a metal dz2-orbital)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 100 publications
0
4
0
Order By: Relevance
“…Concerning the results reported in the current work for complexes with Pd, the ρ at BCPs varies between 0.010 and 0.050 au (see Tables S5 and S6, ESI†). The relationship between a classical C–I⋯I XB and I⋯[d z 2 -Pt II ] metal-involving XB in trans -[PtI 2 (NCN(CH 2 ) 5 ) 2 ]·2CHI 3 was discussed by Eliseeva et al 53 In this complex, the source of stabilization is the charge transfer from the metal d z 2 orbital. Therefore, the noted interactions are designated as C–I⋯[d z 2 -Pt II ] metal-involving XBs, where Pt II acts as a d z 2 -nucleophile.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Concerning the results reported in the current work for complexes with Pd, the ρ at BCPs varies between 0.010 and 0.050 au (see Tables S5 and S6, ESI†). The relationship between a classical C–I⋯I XB and I⋯[d z 2 -Pt II ] metal-involving XB in trans -[PtI 2 (NCN(CH 2 ) 5 ) 2 ]·2CHI 3 was discussed by Eliseeva et al 53 In this complex, the source of stabilization is the charge transfer from the metal d z 2 orbital. Therefore, the noted interactions are designated as C–I⋯[d z 2 -Pt II ] metal-involving XBs, where Pt II acts as a d z 2 -nucleophile.…”
Section: Discussionmentioning
confidence: 99%
“…51 The binding between I 2 and various d 8 metals (Pd, Ni, Co, Rh, and Ir) has also been described in van Koten's pincer complex and its 19 alterations. 52 Eliseeva et al 53 found both a classical C–I⋯I XB and metal-including C–I⋯Pt in trans -[PtI 2 (NCN(CH 2 ) 5 ) 2 ]·2CHI 3 , again using the Pt d z 2 orbital as the electron source. It was also reported by Li et al 54 that Ni or Pt metal nanoparticles are able to interact with Na cations, HF or H 2 O based on the local electrostatic contacts between positively and negatively charged areas of subunits from both groups.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, various types of TM•••I interactions were identified [40][41][42][43]. Ni and Pt metal nanoparticles can interact with Na + , HF, and H 2 O, due to the attraction between local positive and negative electrostatic potential regions on the two monomers.…”
Section: Introductionmentioning
confidence: 99%
“…In the overwhelming majority of instances, studies of the “named” noncovalent interactions (i.e., named for an element or a group of elements ) explore nonmetal atoms as coformers exhibiting Lewis basicity. However, it is also established that some positively charged metal ions can function (via their filled d-orbitals) as partners, featuring a negative potential in hydrogen, halogen, chalcogen, , or metallophilic bonding. In contrast to the progress in understanding and the use of these noncovalent forces for supramolecular chemistry, metal-involving PnB has received very little attention.…”
Section: Introductionmentioning
confidence: 99%